Corporate Social Responsibility at Wipro Ltd. - A Case Study - Shah, Shashank (Prabandhan: Indian Journal of Management, 2011)
Corporate Social Responsibility (CSR) has become one of the leading topics of discussion at World Economic Forum Meetings in the last decade and more. It is basically the initiatives an organisation undertakes to positively influence the society in which it exists. The organisation exists in the society, because of the inputs received from it - material and human, and ultimately sells its products and services to it. Hence, every organisation must pay its due in various ways to this important constituency. In this paper, the author has used the case of Wipro Ltd., one of the leading Indian Information Technology (IT) companies, to study their Society and Local Community-related initiatives. The Company has initiated some innovative projects in the field of education, which have also been explored in the case. The data collection for the case has been done by the author through personal interviews with top executives of the Company and supplemented through other information available in the public domain.